Extraction and Analysis of Strontium in Water Sample Using a Sr2+ Selective Polymer as the Absorbent Phase - Rongjian Ying (International Journal of Analytical Chemistry)
A kind of Sr2+ selective resin was applied as an absorption phase to extract Sr2+ ion from an aqueous solution, and the amount of Sr2+ was determined using inductively coupled plasma optical emission spectrometer. Factors, including absorption time, temperature, stirring rate, salt-out effect, desorption, and the pH of the aqueous solution, were investigated to optimize the absorption efficiency of Sr2+. Foreign ions were examined to observe their effects on the absorption behavior of Sr2+. The optimum condition was absorption time at 20 min, pH of aqueous solution 7, temperature of 35°C, and 600 rpm stirring rate. A 10 mL solution of 0.1 mol/L HCl is used as the desorption agent. The linear range of Sr2+ concentrations from 50 to 1200 μg/L was investigated with the slope of 183 μg/L. The limit of detection was 21 μg/L with 4.23% relative standard deviation. The correlation coefficient was found to be 0.9947. Under the optimized conditions, the concentrations of Sr2+ in four water samples were detected by the developed method. We propose that this method effectively extracts strontium ion from environmental water samples.